Innovation, total factor productivity and economic growth in Pakistan: A policy perspective - Hummera Saleem; Malik Shahzad Shabbir; Muhammad Bilal Khan; Bashir Ahmad Khilji (Journal of Economic Structures, 2019)
The objective of this study is to endorse the driving factors behind total factor productivity (TFP) and economic growth in Pakistan. Pakistan's average growth rate is 5% for last few decades, and although this growth level is satisfactory, Pakistan faced several formidable challenges yet. The economic growth has been determined mainly through labor-intensive technology and export-oriented manufacturing activities. However, TFP is assessed from the aggregate production function using the Cobb-Douglas production function that permits for the simultaneous expansion of outputs and contraction of inputs. The annual timer series data have been extracted from 1972-2016 World development Indicator (WDI) for this study. The overall results reveal that almost all variables are statistical significant. Moreover, innovation significantly contributes to economic growth and production level in Pakistan. This analysis may have significant suggestions to policy makers in Pakistan and other emerging economies when framing sustainable growth policy.
Keywords: D24; D33; 330; Innovation; Economic growth; Total factor production; Pakistan